2004
DOI: 10.1002/jmv.20175
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of core promoter and precore stop codon mutants of hepatitis B virus in Vietnam

Abstract: In Asia, genotypes B and C are the most common genotypes of hepatitis B virus (HBV); and genotype C causes more severe liver disease. Core promoter/precore (CP/PC) mutants, known to be linked to these genotypes, could have an impact on the progression and severity of liver disease. Sera of 115 patients, including 39 acute and 76 chronic Vietnamese HBV infected patients, were tested for their liver profile, HBeAg, HBV genotypes, and HBV DNA level. Fragments of 282 nucleotides covering CP/PC were amplified, sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
30
4

Year Published

2007
2007
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 36 publications
7
30
4
Order By: Relevance
“…So far, our study is one of the largest-scale population studies examining the HBV genotype and having the largest population of determining variations in the core promoter and pre-core regions of HBV-DNA in Vietnamese. In agreement with previous studies (25)(26)(27)(28), our results showed that genotypes B and C were the major genotypes in Vietnamese, and that genotype B was more prevalent than genotype C. In the study no cases with genotype A, D, E, F or G were detected. This is the first study to sub-classify genotype B into subgenotype Ba or Bj in Vietnamese and showed that nearly all cases (99.2%) of genotype B were sub-classified into genotype Ba.…”
Section: -------------------------------------------------supporting
confidence: 93%
See 4 more Smart Citations
“…So far, our study is one of the largest-scale population studies examining the HBV genotype and having the largest population of determining variations in the core promoter and pre-core regions of HBV-DNA in Vietnamese. In agreement with previous studies (25)(26)(27)(28), our results showed that genotypes B and C were the major genotypes in Vietnamese, and that genotype B was more prevalent than genotype C. In the study no cases with genotype A, D, E, F or G were detected. This is the first study to sub-classify genotype B into subgenotype Ba or Bj in Vietnamese and showed that nearly all cases (99.2%) of genotype B were sub-classified into genotype Ba.…”
Section: -------------------------------------------------supporting
confidence: 93%
“…This is the first study to sub-classify genotype B into subgenotype Ba or Bj in Vietnamese and showed that nearly all cases (99.2%) of genotype B were sub-classified into genotype Ba. Our results corresponded to those of previous studies of native Vietnamese and Vietnamese immigrants from other countries (17,19,(25)(26)(27)(28)(29)(30)(31), but were inconsistent with the report that genotype A was very common in Vietnamese (33). It was reported that genotype C in East Asia was more strongly associated with severe liver disease and risk of HCC than genotype B (12)(13)(14)(15)20,24,35,37,48,49).…”
Section: -------------------------------------------------contrasting
confidence: 82%
See 3 more Smart Citations